Three new Cryptochetum Rondani, 1875 (Diptera: Cryptochetidae) from Yunnan Province, China and an identification key to Chinese species - Xi, Yuqiang; Yin, Xinming (European Journal of Taxonomy, 2020)
Three species of the genus Cryptochetum Rondani, 1875 from China are described and figured as new to science: C. euthyiproboscise sp. nov., C. glochidiatusum sp. nov., and C. longilingum sp. nov. An identification key to the known species of Cryptochetum from China is presented. The type specimens of the new species are deposited in the Henan Agricultural University.